The law and the control of Aedes in Shah Alam / Siti Khadijah Mohamed Yunus … [et al.] - Mohamed Yunus, Siti Khadijah; Mohd Yusof, Alif Ridhwan; Zakaria, Mohd Norfazli; Zulkarnain, Anas (2009)
This study concerns the law and the control of Aedes in Shah Alam. The method used for this study is qualitative in nature. In 2008 there are 3829 reported cases of dengue all over Malaysia and there is 1385 numbers of reported cases in Selangor. For the fourth week of 2009 there are 688 reported cases of dengue in the locality of Shah Alam alone. Shah Alam holds the highest record for reported dengue cases. The local authority of Shah Alam which is the MBSA, had applied many activities in order to control the outbreak. Among the activities are fogging, health education, public cleaning, distribution of abate, larvaeciding and monitoring. The Act used are the Destruction of Disease-Bearing Insect (Amendment) Act 2000 (Act A 1086), the Prevention and Control of Infectious Disease Act 1988 (Act 342), and Local Government Act 1976 (Act 171). The Act vested the local authority with the power to do anything to safe guard the public health and safety. Among the power vested to them are the powers to fine the offender as in Section 23 of Act A 1086. While Act 342 is used to assist Act A 1086. Act 171 stated the duties of a local government officer in doing their job to prevent the outbreak of any epidemic. Even though there are statutes for preventing the outbreak there is still loop holes in the law. Therefore a review of the Acts must be made in orderto prevent this problem from recurring.